Development of Critical Thinking Scale of Upper Secondary School Students in Social Studies by Applying Computerized Dynamic Assessment - Worathanaphimmakorn, Non; Tangdhanakanond, Kamonwan (Journal of Education Studies, Chulalongkorn University, 2024)
The purposes of this pilot study were 1) to develop the critical thinking scale of upper secondary school students in social studies by applying computerized dynamic assessment, and 2) to validate the critical thinking scale of upper secondary school students in social studies by applying computerized dynamic assessment. The sample consisted of 100 upper secondary school students by purposive sampling. The research instrument used was the critical thinking scale by applying computerized dynamic assessment. Data were analyzed by using content validity, item validation including the difficulty and discrimination indexes, and internal consistency in terms of Cronbach’s alpha coefficient. Results revealed that 1) the critical thinking scale by applying computerized dynamic assessment was two-tier multiple-choice tests (20 items) measuring four components; (1) problem formulation, (2) hypothesis identification and application, (3) data classification and judgment, and (4) conclusion. 2) All items and mixed prompting had content validity (IOC index = .8 to 1.0 and .6 to 1.0), the difficulty and discrimination indexes = .45 to .82 and .41 to .82, and Cronbach’s alpha coefficient = .88.